2020
DOI: 10.3390/s20030940
|View full text |Cite
|
Sign up to set email alerts
|

Percentiles and Reference Values for the Accelerometric Assessment of Static Balance in Women Aged 50–80 Years

Abstract: The identification of factors that alter postural stability is fundamental in the design of interventions to maintain independence and mobility. This is especially important for women because of their longer life expectancy and higher incidence of falls compared to men. The objective of this study was to construct the percentile box charts and determine the values of reference for the accelerometric assessment of the static balance in women. For this, an observational and cross-sectional study with a sample co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Studying the acceleration module is a constant in studies based on accelerometery, and measuring the magnitude of the movement has been used in almost all studies based on accelerometric analysis since this method was first introduced as a tool for assessing balance, both static and dynamic [10,20,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the acceleration module is a constant in studies based on accelerometery, and measuring the magnitude of the movement has been used in almost all studies based on accelerometric analysis since this method was first introduced as a tool for assessing balance, both static and dynamic [10,20,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Selecting a high or low sample rate can also alter the accelerometric record. This frequency must be 50 Hz for the study of postural control [18][19][20]..…”
Section: Instrument and Processing Of Datamentioning
confidence: 99%
“…In addition, the root mean square (RMS) was used as representative value of the three-axis module vector. The accelerometer measurements were configured for a time frame of 1 s. This protocol has already been previously applied and validated both in the adult population and in children [ 23 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…In pediatrics, balance is assessed through low-sensitivity clinical tests, such as the Babinski–Weil Test and the Fukuda Stepping Test, which identify developmental alterations at already advanced stages of deterioration that cannot be detected in earlier stages [ 7 , 8 , 9 ]. Following the implementation of previous studies in adult and older populations [ 10 , 11 ], the use of three-dimensional accelerometers should be generalized to assess postural control in children, providing healthcare professionals and experts in movement and psychomotricity with a quantitative, sensitive and reliable tool that is easy to use and interpret. In fact, a recent systematic review identified accelerometers as instruments that provide reliable information about postural control in a more sensitive manner than clinical test sets traditionally used in the clinical scope.…”
Section: Introductionmentioning
confidence: 99%